KOMUNIKASI VERBAL-NONVERBAL NADIA OMARA TERHADAP KONTEN KISAH HOROR WAWAK EPISODE IZIN PENUNGGU PART 351 MELALUI YOUTUBE - Alfian Jallal Udin Assayuthi; Setefanus Giofani; Filifita Dinda Lestari; Habibah Nur Jamilah; Malik Ibrahim (Nusantara Hasana Journal, 2026)
This study aims to analyze the verbal and nonverbal communication styles used by Nadia Omara in the YouTube content Kisah Horor Wawak Episode Izin Penunggu Part 351. The research is based on communication theory, particularly verbal and nonverbal communication concepts, as well as digital storytelling approaches. A qualitative descriptive method was employed by analyzing the video transcript and observing communication elements such as diction, intonation, facial expressions, and gestures. The results show that Nadia Omara utilizes an expressive and persuasive communication style through the use of informal language, repetitive expressions, and dramatic narration. Nonverbal elements, including voice modulation, pauses, and facial expressions, play a crucial role in building tension and emotional engagement. The integration of verbal and nonverbal communication effectively strengthens storytelling and enhances audience immersion in horror narratives. This study highlights the importance of communication style in digital media content, particularly in creating engaging and emotionally impactful storytelling experiences.